Factors that influence the retention of social volunteers in health: a comparison between the literature and the perception of volunteers - Braz, Raquel pavan; Lima, Gilson Brito Alves (Brazilian Journal of Operations & Production Management, 2020)
Goal: The main objective is to identify the factors that influence the retention of social volunteers in the health area, supported by a comparison between a systematic literature review and the perception of a focus group of volunteers. Design / Methodology / Approach: Word maps have been developed to compare data obtained from the literature review and the perceptions acquired in a focus group. Results: the main findings of the research indicate that the factors that influence the retention of social volunteers in the health area need a more comprehensive and systematic investigation, avoiding that any subject or dimension of analysis is not addressed when trying to evaluate the reasons that influence the permanence in volunteer programs. It was also possible to detect some subjective contexts that may influence the volunteers' behavior and decisions. Limitations of the investigation: The main limitation of the study is the difficulty in generalizing the findings, considering the use of the focus group, which, because it represents a small number of individuals, may not reproduce common sense. Practical implications: This study seeks to collaborate with future research using a methodology that allows us to evaluate whether what has been questioned in research instruments is close to the reality presented by the context. Originality/Value: The novelty concerns in the use of world maps to compare the perceptions of the literature findings with the results of a focus group analysis. This paper seeks to contribute to a new look on the qualitative treatment approach of data obtained in research in this area.